2005
DOI: 10.1254/jphs.fpe05002x
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activities of Propolis Collected by Different Races of Honeybees Against Yeasts Isolated From Patients With Superficial Mycoses

Abstract: Abstract. Yeasts isolated from patients with superficial mycoses were tested against propolis samples collected from different regions and honeybee races. The minimum inhibitory concentration (MIC) values obtained using the agar dilution methods were compared to the diameters of growth inhibition zones by using the disk diffusion method. The results showed that Candida albicans, C. glabrata, Trichosporon spp., and Rhodotorula sp. were susceptible to low concentrations of propolis, the latter showing a higher s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 28 publications
1
61
1
3
Order By: Relevance
“…In the present study, the most commonly used concentration of propolis (10% EEP) was selected for testing (7,25,26), and its effectiveness was found to be limited when compared to the other chemical disinfectants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the most commonly used concentration of propolis (10% EEP) was selected for testing (7,25,26), and its effectiveness was found to be limited when compared to the other chemical disinfectants.…”
Section: Discussionmentioning
confidence: 99%
“…Presented at the poster session, the 19th meeting, Balkan Stomatological Society, Belgrad, Serbia, April [24][25][26]2014.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18][19][20][21] In Southwestern Algeria, propolis used by beekeepers and little is known about its biological activities. A study of Boufadi et al (2014) reported that propolis harvested from different areas of Algeria contained various high concentrations of polyphenolic compounds known as the main active molecules exhibited free radical scavenging activity.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Studies of toxicology suggested that Cd is a risk factor associated with prostate cancer. 20,28,29 The cellular mechanism of Cd toxicity was already elucidated. After Cd absorption, Cd is transported by albumin and hemoglobin to reach the liver.…”
Section: Discussionmentioning
confidence: 99%